INDONESIAN LEARNING WITH A GENRE-BASED APPROACH FOR BIPA STUDENTS AT SOUSSE UNIVERSITY, TUNISIA - Idris, As Rakhmad (ppjbsip, 2021)
This study seeks to explore the stages of BIPA learning at Sousse University, Tunisia, which uses a genre-based approach. The design of this study is qualitative and is described descriptively. Indonesian language skills including writing skills are the focus of this research. This study uses observation data, worksheets, and questionnaire results. Based on the results of the analysis conducted, it was found that there was an increase in learner skills. Also found obstacles faced by teachers as a form of evaluation for the sending of teaching staff in the following year. Lack of teaching staff and time allocation are problems of text-based learning that requires repetition and focus on the learner. The research also found that the genre-based approach was very effective to be used in the classroom and filled with a small number of students. This research is expected to be a proposal for policies for the management of BIPA learning abroad.AbstrakPenelitian ini berupaya mengeksplorasi tahapan pembelajaran BIPA di Universitas Sousse, Tunisia, yang menggunakan genre-based approach. Desain penelitian ini bersifat kualitatif dan dipaparkan secara deskriptif. Keterampilan berbahasa Indonesia termasuk di dalamnya keterampilan menulis menjadi fokus penelitian ini. Kajian ini menggunakan data amatan, lembar kerja, dan hasil kuesioner. Berdasarkan hasil analisis yang dilakukan, ditemukan peningkatan keterampilan pemelajar. Ditemukan juga kendala yang dihadapi pengajar sebagai bentuk evaluasi bagi pengiriman tenaga pengajar di tahun berikutnya. Kekurangan tenaga pengajar dan alokasi waktu merupakan problematika pembelajaran berbasis teks yang membutuhkan pengulangan dan fokus pada pemelajar. Penelitian ini juga menemukan bahwa pendekatan genre-based sangat efektif digunakan di kelas dalam dan diisi jumlah pemelajar yang tidak banyak. Penelitian ini diharapkan dapat menjadi usulan bagi kebijakan bagi pengelolaan pembelajaran BIPA di luar negeri.